LOW-TEMPERATURE MAGNETIZATION AND AC SUSCEPTIBILITY OF MAGNETITE: EFFECT OF THERMOMAGNETIC HISTORY - Kosterov A. (My University, 2003)
Saturation isothermal remanent magnetization (SIRM) and AC susceptibility have been measured as a function of temperature between 5 K and room temperature for one multidomain and three pseudo-single-domain magnetite samples after cooling in a zero (ZFC) and in a strong magnetic field (FC), and also after three partial field coolings (PFC) when a magnetic field had been turned on in 300-150, 150-80 and 80-5 K ranges, respectively. For the multidomain sample, SIRM(5 K) after ZFC is about twice as high as after FC, while the low-field susceptibility is higher after FC. SIRM and susceptibility curves measured after PFC(300-150 K) and PFC(150-80 K) coincide with those measured, respectively, after ZFC and FC. PFC(80-5 K) curves are intermediate between the two extremes. This behaviour can be fairly well understood within the framework of a simple model, introduced back in the 1950s, which assumes that on cooling through the Verwey transition in a strong magnetic field easy magnetization axes in the low-temperature phase are set along the [001] directions of the high-temperature (cubic) phase closest to the field direction. If, on the other hand, the Verwey transition is passed in a zero field and a strong magnetic field is applied below the transition temperature, some of easy axes, initially set at random, can still be switched into the field direction, explaining observed SIRM and susceptibility versus temperature curves measured after PFC(80-5 K). Pseudo-single-domain grains show a more complex behaviour, which depends strongly on sample stoichiometry. In two samples with a relatively small non-stoichiometry (Verwey temperatures are 122 and 110 K, respectively) SIRM(5 K) is higher by 5-7 per cent after FC. After both PFC(150-80 K) and PFC(80-5 K), SIRMs are nearly equal in magnitude to SIRM acquired after FC, but are thermally demagnetized at a different rate below the Verwey transition. Low-field susceptibilities also show different temperature dependences below $TV $, dependent on a preceding thermomagnetic treatment. A strongly non-stoichiometric sample $(TV = 95 K)$ shows very large, over 70 per cent, difference between SIRMs after FC and ZFC, respectively, and a 35 per cent difference between susceptibilities measured under the same conditions. These results suggest that in magnetite grains several microns in size, easy magnetization axes setting on first passing the Verwey transition from above and switching of easy axes on subsequent cooling below the transition occur, qualitatively, in the same way as in grains of larger size, but switching of easy axes is considerably facilitated. The latter process is subject to further enhancement in strongly non-stoichiometric magnetite, where it seems to be possible even in zero field, resulting in SIRM, susceptibility and magnetic hysteresis properties fairly different from more stoichiometric samples. Strongly depressed, compared with stoichiometric magnetite, magnetocrystalline anisotropy of the low-temperature phase could be a physical mechanism for this behaviour.
Keywords: MAGNETIC DOMAINS; MAGNETITE; VERWEY TRANSITION